Quality of life scale in parkinson's disease PDQ-39 - (Brazilian Portuguese version) to assess patients with and without levodopa motor fluctuation Escala para qualidade de vida na doença de Parkinson - PDQ 39 (versão do Português falado no Brasil) como instrumento para avaliação de pacientes com e sem flutuação motora decorrente da levodopa - Renata Guzzo Souza; Vanderci Borges; Sonia Maria Cesar de Azevedo Silva; Henrique Ballalai Ferraz (Arquivos de Neuro-Psiquiatria)
Quality of life (QoL) is an important treatment outcome indicator in Parkinson's disease (PD). The aim of this study is to assess the usefulness of the Parkinson's disease questionnaire - PDQ-39 (Brazilian Portuguese Version) in measuring QoL of PD patients with or without motor fluctuations. Fifty-six PD patients with mean disease duration of 7.4 years were assessed and 41 of them (73.3%) had motor fluctuations. The PDQ-39 has eight dimensions ranging from 0 to 100; being the higher the score, the worse the QoL. Comparing groups with and without motor fluctuations showed that the dimensions mobility, activities of daily living (ADL), communication and bodily discomfort scored higher in the fluctuating group. There was a tendency to see that the higher the Hoehn and Yahr (HY) scale stages, the higher the PDQ-39 scores. Patients suffering from the disease for more than five years had worse PDQ-39 scores only in the items ADL and communication, when compared with those with the disease for < 5 years. The PDQ-39 is an instrument that detects decrease in QoL of PD patients and the presence of motor fluctuations predicts QoL reduction. A qualidade de vida (QdV) é um item importante para se mensurar o sucesso do tratamento na doença de Parkinson (DP). O objetivo deste estudo foi o de avaliar a utilidade do questionário sobre a doença de Parkinson - PDQ-39 (versão em língua portuguesa falada no Brasil) para mensurar a QdV dos pacientes parkinsonianos com e sem flutuação motora. Nós avaliamos 56 pacientes com DP com tempo médio da doença de 7,4 anos, e destes 41 (73,3%) apresentavam flutuação motora. A PDQ-39 tem oito domínios que variam de 0 a 100 e quanto maior o escore pior a QdV. A comparação dos grupos de pacientes com e sem flutuação motora mostrou que os domínios: mobilidade, atividades de vida diária, comunicação e desconforto corporal tinham escores maiores nos flutuadores. Quanto maiores os estágios de Hoehn e Yahr (HY) da doença, maiores os escores da PDQ-39. Pacientes com mais de 5 anos de evolução da doença mostraram escores piores da PDQ39 apenas nos itens atividades da vida diária e comunicação se comparados a pacientes com 5 anos ou menos de doença. A PDQ-39 é um instrumento capaz de detectar declínio da QdV de pacientes com DP e a presença de flutuação motora é um preditor para redução na QdV.